Three-dimensional CuO microflowers as anode materials for Li-ion batteries. Issue 6 (July 2015) - Hu, Zhongli; Liu, Hongdong
Abstract: It is well-known that transition metal oxides are promising anode materials for Li-ion batteries because of their high theoretical capacity and good capacity retention properties. Here we have synthesized copper oxide microflowers (CuO-MFs) by solid-state thermal conversion of Cu(OH)2 precursors. The crystal structure, surface morphology, and electrochemical performance of the products were deeply investigated by X-ray diffraction, scanning electron microscopy, and galvanostatic charge/discharge, respectively. The results suggest that CuO-MFs as novel anode materials have exhibited excellent electrochemical performance in Li-ion batteries. The initial discharge capacity is 785 mA h g −1, and the reversible capacity is still maintained at 350 mA h g −1 after 50 cycles. Thus, three-dimensional CuO-MFs provide a new insight into the development of anode materials for next-generation high-performance Li-ion batteries.